Academic motivation of adolescent Jamaican girls in selected single sex and coeducational schools - McMillan, Veta (1981)
This study investigated whether girls in selected Jamaican high schools differed in their level of academic achievement motivation according to their placement in single-sex or co-educational schools, through an examination of their academic self-concept, their perception of sex roles, their lifestyle, and their academic achievement motivation. A battery of four tests was used to gather data from a sample of 91 first form students (47 coed, 44 single-sex) and 157 fourth formers (81 coed, 76 single-sex) from four schools in both urban and rural areas. Results of the data analysis revealed significant differences in the academic self-concepts of students at urban as against rural schools, the latter having a higher estimate of their abilities. A significant relationship existed between academic self-concept and academic motivation for the total sample. A significant inverse relationship between lifestyle and the perception of sex roles also emerged. No significant difference was found between the academic motivation of first and fourth formers, or between girls attending different types of schools
Keywords: Single-sex schools